Making or un-making states: when does war have formative effects? - Jüde, Johannes (European Journal of International Relations, 2022)
“War made the state, and the state made war” is Charles Tilly’s famous dictum that has become highly influential both in comparative macrosociology and in International Relations. An extensive literature suggests that this mechanism has played a pivotal role in European processes of state formation. However, its applicability to warfare in the Global South is controversial. While some argue that the relationship remains the same, others are skeptical of the effects of the bellicist mechanism. Against the background of the debate as to whether war makes or un-makes states in the Global South, this paper examines the conditions under which wars have formative effects and result in state-making. Revisiting the war-making/state-making paradigm, I argue that the mode of economic reproduction of “wielders of coercion” determines whether war has formative effects. Wielders of coercion, or more specifically, non-state armed movements may draw on (1) rents, (2) indirect extraction, or (3) direct extraction to sustain their economic base and organize coercion. However, they institutionalize and develop into a state-like organization only when they rely on direct extraction. To support these claims, I conduct a plausibility probe drawing on evidence from highly successful armed insurgencies: Eritrea’s EPLF, Somaliland’s SNM, and Namibia’s SWAPO. In sum, the bellicist relationship remains valid for the Global South, even if the conditions under which war makes states are rare. A more nuanced reading of the bellicist theory improves our understanding of the dynamics of state formation and decay in the post-colonial world.
CRIS-Team Scopus Importer:2021-11-05
Keywords: bellicist theory; conflict; Global South; insurgents; organization of coercion; State formation